The Study of Xi ‘an Unitary Settlements’ Redevelopment Strategy in “Mobility Space” Aspect - Hu Miaofen; Yan Shuiyu (Lodz University of Technology Press, 2023)
In the 1950s, during the period of Chinese socialist collective economy, many unit-system urban settlements were formed that served the employees of the same enterprise, with cohesive space, complete functions, and independent land use as the basic spatial units. The migration of people, goods and capital had led to a dramatic ‘spatial reorganisation’ of these unitary urban areas. This paper selects the unitary settlements of the third, fourth and fifth factories of the State Cotton Factory in the Fangzhi City area of Xi'an as the research target. With the help of emerging network data and ArcGIS visualisation, using multiple sources of data to build a matrix of human, logistics, capital, information and traffic flows to study the network structure and node structure of mobility links at the block scale and obtain the development status and spatial network structure of the unitary settlements in the Fangzhi City area. The research shows that the flow connection network group is closely connected and the social network analysis subgroup structure is clear. Based on the existing form and development trend of this kind of flow space, a redevelopment strategy for unit-based residential quarters adapted to flow is proposed to comprehensively improve the quality and vitality of the community.
Keywords: flow space; space redevelopment; unit system residents; Xi'an Fangzhi City; przestrzeń przepływu; przebudowa przestrzeni; mieszkańcy układu jednostek; miasto Xi'an Fangzhi